(untitled) (Jurnal Pembangunan Perikanan dan Agribisnis, 2026)
Rig to Reef is a marine environmental management approach that involves repurposing decommissioned Offshore Oil and Gas Platforms (OOGP) into artificial reefs. The success of this program largely depends on synergy and active participation from various stakeholders. This study aims to identify the potential, roles, and levels of influence and interest of stakeholders in managing the Rig to Reef program in Bontang City. The research was conducted from April to July 2025 using a qualitative descriptive method. Data collection techniques included in-depth interviews, field observations, and document studies. Respondents were selected through purposive sampling, consisting of nine key stakeholders representing government agencies and community groups. Analysis was carried out using an interest–influence quadrant mapping to determine stakeholder positions and assess collaborative strategies for managing the Rig to Reef program. The results show that stakeholders are divided into four categories: Key Players, Subjects, Context Setters, and Crowd. The Ministry of Marine Affairs and Fisheries is positioned as a Key Player, while the Coastal and Marine Resource Management Office of Pontianak, the East Kalimantan Provincial Marine and Fisheries Office, the Environmental Agency, and the Marine and Fisheries Resources Surveillance fall under the Subjects category. Further analysis suggests relevant collaboration strategies, including enhancing cross-sectoral coordination, actively involving fishing groups and community monitors, and fostering partnerships with the private sector, particularly oil and gas companies. The identified priority strategy is the establishment of a permanent stakeholder communication forum to strengthen synergy and support the sustainability of the Rig to Reef program in Bontang.